Penentuan Prioritas Risiko pada Rancangan Rantai Pasok Biodiesel dari Minyak Goreng Bekas di Kota Padang - Kurnia, Ruri; Hadiguna, Rika Ampuh (Universitas Katolik Parahyangan, 2016)
A design of biodiesel supply chain from waste cooking oil conducted in previous studies. Implementation of supply chain design needs to be studied more in depth and comprehensive. One aspect of the study is a supply chain risk management. Supply chain risk management is important because many events in supply chain which raises operational problems and the cessation of business activity. Because of vulnerability of the supply chain to various internal and external risks, the study of risk sources is needed. This study examines the sources of risk and the weighting that may occur along the supply chain for the distribution of biodiesel from waste cooking oil from suppliers that located in various places until the sale of biodiesel to consumers that are targeted to the public in Padang. The method used in this research is fuzzy AHP with triangular fuzzy number approach. Risk identification is done with the study of literature and assessment by experts. Based on the results obtained sequences risks from largest to smallest weight are raw materials, market, quality, production, transportation, and partnerships.